2007
DOI: 10.1103/physreva.75.033617
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum limits to center-of-mass measurements

Abstract: We discuss the issue of measuring the mean position ͑center of mass͒ of a group of bosonic or fermionic quantum particles, including particle number fluctuations. We introduce a standard quantum limit for these measurements at ultralow temperatures, and discuss this limit in the context of both photons and ultracold atoms. In the case of non-interacting harmonically trapped fermions, we present evidence that the Pauli exclusion principle has a strongly beneficial effect, giving rise to a 1 / N scaling in the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Mathematically, the difference between the predictions of the many-body and mean-field descriptions can be tracked down to the subtlety of performing the infinite-particle limit only after (and not before) the many-particle operator is evaluated. In comparison with the variance of an operator of a single particle, the variance of many-particle operators is a much richer quantity, also see [22][23][24][25] in this context. At the bottom line, the many-body and mean-field wave-functions themselves differ at the infinite-particle limit and, consequently, their overlap is always smaller than one and can become arbitrarily small [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematically, the difference between the predictions of the many-body and mean-field descriptions can be tracked down to the subtlety of performing the infinite-particle limit only after (and not before) the many-particle operator is evaluated. In comparison with the variance of an operator of a single particle, the variance of many-particle operators is a much richer quantity, also see [22][23][24][25] in this context. At the bottom line, the many-body and mean-field wave-functions themselves differ at the infinite-particle limit and, consequently, their overlap is always smaller than one and can become arbitrarily small [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…d) Concerning the experimental and theoretical limits put on the measurements of position (center of mass) of an atom, see Refs. [55,56]. In this case, the uncertainty of the localization (of the order of nanometers) is much bigger than the Compton wavelength of the atom itself!…”
Section: Discussionmentioning
confidence: 99%
“…[33], where it is shown that it is only possible to measure mutual relative positions of atoms. Regarding their absolute positions the best localization of atoms which can be realized is at the level of hundred of nanometers [34,35], much higher than the atom Compton wavelength.…”
Section: B Non-relativistic Casementioning
confidence: 99%